Role of exchange interaction in nitrogen vacancy center based magnetometry - Ho, Cong Son (2017)
We propose a multilayer device comprising a thin-film-based ferromagnetic heterostructure (FMH) deposited on a diamond layer doped with nitrogen vacancy centers (NVC's). We find that when the NVC's are in close proximity (1–2 nm) to the FMH, the exchange energy is comparable to, and may even surpass, the magnetostatic interaction energy. This calls forth the need to consider and utilize both effects in magnetometry based on NVC's in diamond. As the distance between the FMH and NVC is decreased to the subnanometer scale, the exponential increase in the exchange energy suggests spintronic applications of NVC's beyond magnetometry, such as detection of spin Hall effect or spin currents.